Digital Leadership, Organizational Support, and Non-ASN Employee Performance: The Mediating Role of Job Satisfaction - Anwari Firdaus Ramadhan; Maman Suratman (Golden Ratio of Human Resource Management, 2026)
Digital transformation in the public sector is crucial, but the 2023 National SPBE Index ranked it "sufficient" and West Java Province ranked it "good." This creates a gap in human resource competency and technology utilization, exacerbated by low digital literacy among regional employees. Empirically, there was a decline in digital leadership scores, organizational support, job satisfaction, and performance of non-civil servant employees in Department X, West Java Province, during the 2024–2025 period, indicating suboptimal implementation of digital transformation. The main problem lies in the lack of synergy between leadership's digital orientation and organizational support, such as limited budgets, training, facilities, and reward systems, which impacts employee job satisfaction and performance. This study used quantitative methods by distributing questionnaires to 62 employees and then analyzing them using structural equation modeling to examine the relationships between variables.Digital leadership and job satisfaction were rated good, organizational support very good, and employee performance fair. Digital leadership and job satisfaction significantly improved performance, while organizational support had no direct effect. However, both digital leadership and organizational support positively influenced job satisfaction, which mediated their impact on performance. In conclusion, performance improvement is more effectively achieved by strengthening digital leadership and increasing job satisfaction, rather than relying solely on organizational support.